Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian pada Shopee.co.id - Viska Agustiani; Umban Adi Jaya (Institut Manajemen Wiyata Indonesia, 2022)
Shopee on National Online Shopping Day (Harbolnas) 12.12.2020 recorded the highest sales record of one million products in one minute, and 12 million products in 24 minutes. This study aims to examine purchasing decisions at Shopee.co.id when viewed from the influence of product quality and promotions carried out. The research method uses a quantitative approach. The research instrument used a questionnaire distributed to 100 respondents, namely students in Sukabumi City. The test instruments include validity and reliability tests. Data analysis used multiple linear regression analysis consisting of hypothesis testing and F test. The results of this study found that product quality and promotion had no effect, either partially or simultaneously, on purchasing decisions at Shopee students in Sukabumi City. It is not easy to ensure the quality of the products that come after shopping online. Massive promotional activities carried out by various platforms create many choices for potential consumers to make purchasing decisions